Meretseger: A Reexamination - Anderson, Parker M. (AUC Knowledge Fountain, 2024)
Meretseger, “She Who Loves Silence,” the cobra goddess of the Theban necropolis and local deity of Deir el-Medina, is well attested for in the New Kingdom. This single sentence makes up most of the information in publications today, derived from Bernard Bruyère’s Mert Seger à Deir el Médineh (1929-1930), the only study dedicated to the “Mistress of the West.” Since then, new evidence has been found after 1930 and has not been compiled into a single publication until now. This thesis will reexamine Meretseger to form a more accurate, up-to-date study of her attestations and iconographic representations and trace her chronology as a goddess. Using Bruyère’s monograph as a foundation and more recent scholarships, archaeological material, iconographical, and textual evidence to further the understanding of the goddess Meretseger.